Chapter Introduction - Woźniak-Jęchorek, Beata (Routledge Studies in Labour Economics, 2023)
This book focuses on the impact of the COVID-19 pandemic on changing labour markets and accelerating digitalisation of the workplace in Central and Eastern Europe. The COVID-19 pandemic disrupted workplaces substantially. As the lockdowns or stay-at-home measures entered into force, a large proportion of the workforce was instructed to stay home and continue to work remotely if their functions made it possible. This policy accelerated the introduction of many digital solutions, requiring the establishment of new patterns of work, and new institutional logic guiding daily activity for both organisations and individuals. In a relatively short time, remote working has become a kind of commonly accepted new institution with its own new logic, structures, rules, and behaviours (Jacks, 2021). The trends contributing to a shift towards more flexible, digital working patterns were emerging before the pandemic (over the last decade) in response to societal developments, the increasing participation of women, and greater global competition. In 2020, the combined health and economic shocks have only deepened the concerns about technology-driven displacement of jobs, growing income inequality, and rising societal discord towards globalisation.